Cephapirin Intervention for Improved Fertility in Repeat Breeder Buffaloes with Subclinical Endometritis - Gond, Malasri; Bijurkar, Rajeshwar Gangaram; Doddagoudar, Venkanagouda; Pasha, Mohammad Mujaheed; Tandle, Manik Kishanrao (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
This pilot study was conducted to check the intervention of cephapirin on the reproductive performance of repeat breeder buffaloes with subclinical endometritis. Endometrial cytology by cytobrush technique was used to diagnose the subclinical endometritis and selected animals (n=12) were randomly divided in two equal groups. Group-I buffaloes were not given any treatment, whereas Group-II buffaloes were administered with benzathine cephapirin once intrauterine. The recovered animals were inseminated at subsequent estrus and pregnancy diagnosis was performed 60 days later. The recovery rate and conception rate were significantly higher (p≤0.05) in Group II (83.33 and 80.00 %) as compared to Group I (0 % each). Based on the results, it can be concluded that Cephapirin (Metricef®) was effective in repeat breeder buffaloes with subclinical endometritis.